Identification of Kappaphycus alvarezii seaweed based on phylogenetic and carrageenan conten - Satriani, Gloria Ika; Tri Soelistyowati, Dinar; Alimuddin; Arfah, Harton; Effendi, Irzal (Jurnal Akuakultur Indonesia, 2024)
Increasing seaweed production requires accurate information regarding the genetic sources of seeds used. Identifying the seaweed species Kappaphycus molecular is one of the solutions to ensure seaweed cultivators choose seeds for their cultivation businesses. Molecular identification is essential for the system traceability of seaweed products and the creation of databases regarding species variant information Kappaphycus alvarezii cultivation as potential data collection for developing and genetically breeding seaweed seeds. To date, there is no information on the genetic potential of K. alvarezii cultivated in various seaweed cultivation centers in Indonesia. This study aimed to obtain phylogenetic details based on identification of the genetic source using DNA molecular markers barcoding rbcL and analysis of carrageenan content using the Fourier transform infra-red (FTIR) spectrum. The results of DNA sequencing analysis and FTIR testing of 16 varieties of seaweed seedlings obtained from various cultivation centers in Indonesia showed 99% similarity with K. alvarezii, a producer of kappa carrageenan. Keywords: DNA sequencing, phylogenetics, haplotypes, kappa-carrageenan, rbcL ABSTRAK Peningkatan produksi rumput laut memerlukan informasi yang akurat mengenai kepastian sumber genetik bibit yang digunakan. Identifikasi spesies rumput laut Kappaphycus secara molekuler merupakan salah satu solusi untuk memberikan kepastian pada pembudidaya rumput laut untuk memilih bibit bagi usaha budidaya. Identifikasi molekuler sangat penting dalam sistem traceability produk rumput laut dan pembuatan basis data mengenai informasi varian spesies Kappaphycus alvarezii budidaya sebagai pendataan potensi untuk pengembangan dan pemuliaan bibit rumput laut secara genetis. Sampai saat ini belum tersedia informasi mengenai potensi genetik rumput laut K. alvarezii yang dibudidayakan di berbagai sentra budidaya rumput laut di Indonesia. Penelitian ini bertujuan untuk memperoleh informasi filogenetik berdasarkan identifikasi sumber genetiknya menggunakan penanda molekuler DNA barcoding rbcL serta analisis kandungan karaginannya menggunakan spektrum Fourier Transform Infra-Red (FTIR). Dari hasil analisis sekuensing DNA dan pengujian FTIR terhadap 16 varietas bibit rumput laut yang diperoleh di berbagai sentra budidaya di Indonesia menghasilkan 99% kemiripan yang tinggi dengan K. alvarezii penghasil kappa karagenan. Kata kunci: DNA sekuensing, filogenetik, haplotipe, kappa-karagenan, rbcL